Decreased Weight Loss Following Bariatric Surgery in Patients with Type 2 Diabetes - Rebelos Eleni; Moriconi Diego; Honka Miikka-Juhani; Anselmino Marco; Nannipieri Monica (SPRINGER, 2025)
Background: Bariatric surgery represents the most effective treatment for achieving significant and sustained weight loss. We aimed to assess whether presence of type 2 diabetes (T2D) at baseline, and T2D remission following bariatric surgery affect the weight loss outcome.
Methods: Data of 312 consecutive morbidly obese subjects who underwent bariatric surgery were analysed. Patients underwent either RYGB (77%), or sleeve gastrectomy (23%), and their body weight was followed-up for 1, 2, 3, 4, and 5 years at regular ambulatory visits (N = 269, 312, 210, 151, 105, at each year, respectively). T2D remission was assessed according to the ADA criteria.
Results: In the whole dataset, 92 patients were affected by T2D. Patients with T2D were older than patients without T2D (52 +/- 9 vs 45 +/- 11 years, p < 0.0001), but there were no differences in baseline BMI, sex, and type of intervention received. We found that presence of T2D at baseline was associated with smaller weight loss at 1, 2, 3, 4, and 5 years following bariatric surgery (delta BMI at 2 years: - 13.7 [7.7] vs - 16.4 [7.3] kg/m(2); at 5 years - 12.9 [8.8] vs - 16.3 [8.7] kg/m2 in patients with T2D vs patients without T2D respectively, all p < 0.05). When dividing the patients with T2D in remitters and non-remitters, non-remitters had significantly smaller weight loss compared to remitters (delta BMI at 2 years: - 11.8 [6.3] vs - 15.4 [7.8] kg/m2; at 5 years: - 8.0 [7.1] vs - 15.0 [7.2] kg/m2, non-remitters vs remitters respectively, all p < 0.05).
Conclusions: T2D is independently associated to smaller weight loss following bariatric surgery, especially in subjects not achieving diabetes remission.